Handbook of optics - Bass, Michael (McGraw-Hill, 1995)
Gives you access to information concerning areas of modern optics. Prepared under the auspices of the Optical Society of America, this work includes the information you need to start solving problems in optics, from design of optical systems to day-to-day laboratory research and development.